Some Characteristics of Theological Terms Borrowed from Arabic Language (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Religion has become an important factor in social life. There are many countries where religion is the leading ideology nowadays. Many countries pay great attention to this direction in the field of linguistics. Accordingly, studying the religious lexicon is one of the urgent issues. In Uzbek linguistics, a lot of work has been done on the study of lexical and thematic groups: kinship terms, action verbs, color-adjective terms, types of building names, etc. But the Supreme Being and other names used around him have not been studied yet. Studying the theonymic lexicon is characteristic not only for linguistics and philology, but also for history, philosophy, and religious studies.